The effect of community interventions in reducing burns and scalds in children. (1st March 2011) - Weerasinghe, A; Ha, H; Hartley, D; Khan, A A
Abstract : Objective: This paper reviews the effect of a variety of community-based interventions in preventing burns and scalds in children. It also highlights how clinical research can be used to improve public health and awareness. Design: The baseline research has already been carried out in the Bradford Burn Study which reviewed burn attendances to an inner city emergency department. The highest incidence of burns was in children below 10 years (36%) with 1 year olds being the largest group affected. Strategies have been put in place by community bodies to address this problem. Interventions: A number of community-based interventions have been initiated. These include A burns doll which can be used in health promotion activities and child safety is integral to the Health Visiting Service. A hot drinks campaign in toddler groups and setting up of a Hot Drink Zones have changed practice. Safety leaflets focusing on the issues of burns in children have been produced. The information for the study has also been used in the Stay Safe event which has been facilitated by St Johns Ambulance Service. Further work in the community including the Primary care Trust and children's centres has also help spread the message. Conclusion: This poster has demonstrated that a multifaceted strategy to reduce burns and scalds in children can be initiated by community teams. It is paramount that good quality clinical data can be made available so that effective change can occur in the field of child safety.